WORKFORCE DEVELOPMENT AND ORGANIZATIONAL PERFORMANCE: A STUDY ON TRAINING INTERVENTIONS IN SMALL-SCALE INDUSTRIES OF CHANDRAPUR - Pedulwar, Suraj Banduji; Sheikh, Niyaj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Workforce development is important to build capacity in employees and helps achieve better overall results of an organisation. Hence, the present study was undertaken to know the effect of training on the productivity and development of small-scale industries in Chandrapur district. The study examines different training programs, their implementation methods, and their impact on productivity, skill improvement, and job satisfaction. Other studies: A mixed-method approach, which included surveys and interviews, was used to evaluate the success of training initiatives. These factors make part of the positive correlation between structured training programs and improved workforce efficiency, reduction in the culture of employee turnover and better organization performance. Critical issues affecting small-scale industries in interventions and recommendations for workforce development interventions for growth are identified.